WRESTLING WITH SCHIZOPHRENIA IN THE NOVEL CHALLENGER DEEP (2015) BY NEAL SHUSTERMAN - Rasyidah Elqayyimah; An Fauzia Rozani Syafei (English Language and Literature, 2019)
The purpose of this analysis is to expose the issue about wrestling with schizophrenia which is done by protagonist and to know the contribution of setting, character and plot in revealing the issue about wrestling with schizophrenia. This analysis is related to the medical theory of schizophrenia and the concept of id, ego, and superego by Sigmund Freud. This analysis is supported by the text and context based interpretation. The result of this analysis shows the protagonist succeeds in wrestling with schizophrenia through self-controlling and socializing with others.